2010
DOI: 10.1016/j.jnt.2009.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Mean values with cubic characters

Abstract: We investigate various mean value problems involving order three primitive Dirichlet characters. In particular, we obtain an asymptotic formula for the first moment of central values of the Dirichlet L-functions associated to this family, with a power saving in the error term. We also obtain a large-sieve type result for order three (and six) Dirichlet characters.Comment: 22 pages; greatly shortened, simplified and corrected versio

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(105 citation statements)
references
References 13 publications
3
102
0
Order By: Relevance
“…This generalization of the classical large sieve inequality to sparse moduli sets, usually given as values of some fixed polynomial, has been studied intensely in past research and has already influenced some other areas of Number Theory, especially the version with k = 2 from [2]. To name a few such topics, it has been found useful to find variants of Bombieri-Vinogradov's theorem [4,13], new results on primes of polynomial shape [9] or primes in APs to spaced moduli [4], divisibility questions with Fermat quotients [8], and mean value estimates for character sums with applications [1,3,5,16]. Furthermore, the multidimensional polynomial LSI can be used for sieving with high powers like seen in [12] and reaches questions related to the abc-conjecture.…”
Section: Second Application: the Polynomial Large Sieve Inequality (Lmentioning
confidence: 99%
“…This generalization of the classical large sieve inequality to sparse moduli sets, usually given as values of some fixed polynomial, has been studied intensely in past research and has already influenced some other areas of Number Theory, especially the version with k = 2 from [2]. To name a few such topics, it has been found useful to find variants of Bombieri-Vinogradov's theorem [4,13], new results on primes of polynomial shape [9] or primes in APs to spaced moduli [4], divisibility questions with Fermat quotients [8], and mean value estimates for character sums with applications [1,3,5,16]. Furthermore, the multidimensional polynomial LSI can be used for sieving with high powers like seen in [12] and reaches questions related to the abc-conjecture.…”
Section: Second Application: the Polynomial Large Sieve Inequality (Lmentioning
confidence: 99%
“…where g is a smooth compactly supported function arising from the partition of unity and the support of g is in the interval [1,2]. As noted in [28], it suffices to show that…”
Section: General Approachmentioning
confidence: 99%
“…Soundararajan [15] has shown that at least 7/8 of the central values in the family of quadratic Dirichlet L-functions are nonzero. More recently, Baier and Young [2] consider the family of Dirichlet L-functions associated to cubic and sextic characters and show that infinitely many (though not a positive proportion) of these functions are not zero at the central point.…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%